Increased circulating follicular regulatory T cells in Hashimoto's thyroiditis - Jiwei Zhao; Yanxia Chen; Zhenyao Xu; Wei Yang; Zhongliang Zhu; Yingxiang Song; Jinlin Liu (Taylor & Francis Group, 2018)
Objective: Follicular T helper (Tfh) cells are involved in the pathogenesis of Hashimoto's thyroiditis (HT), while follicular T regulatory (Tfr) cells inhibit Tfh cells, which mediate B cell responses. However, the role of Tfr cells in HT remains unclear. Methods: Forty-six healthy controls (HCs) and 84 HT patients were enrolled in the study. The percentage of Treg cells, CXCR5− Treg cells, and Tfr cells; the Tfr/Tfh ratio; and the percentage of ICOS, PD-1, CTLA-4, CXCR3 and CCR6 in Tfr cells were investigated; furthermore, the associations between the percentage of Tfr cells or the Tfr/Tfh ratio and the autoantibody indices were investigated. Results: Compared with that in the HCs, the percentage of Treg cells in the HT patients was not significantly changed, but the percentage of CXCR5− Tfr cells was decreased. In contrast, both the percentage of Tfr cells and the Tfr/Tfh ratio were significantly increased in the HT patients. Among the Tfr cells, the percentage of Th2-like Tfr cells was increased in the HT patients, while the percentage of Th17-like Tfr cells was decreased. Moreover, the percentages of ICOS and PD-1 on Tfr cells were significantly increased in the HT patients, while the percentage of CTLA-4 on Tfr cells was significantly decreased. However, the percentage of ICOS, PD-1 and CTLA-4 on Treg or CXCR5− Treg cells was not significantly changed. Last, no association was found between either the percentage of Tfr cells or the Tfr/Tfh ratio and the antithyroglobulin and antithyroid peroxidase antibody levels in the HT patients. Conclusions: In the HT patients, the circulating Tfr cell percentage and Tfr/Tfh ratio were significantly increased, but the humoral immune function of Tfr cells might be impaired.